1999
DOI: 10.1161/01.hyp.34.6.1281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the HMG-CoA Reductase Inhibitors on Blood Pressure in Patients With Essential Hypertension and Primary Hypercholesterolemia

Abstract: Abstract-Certain hydroxymethylglutaryl coenzyme A reductase inhibitors, ie, statins, may cause vasodilation by restoring the endothelial dysfunction that frequently accompanies hypertension and hypercholesterolemia. Several studies have found that a blood pressure reduction is associated with the use of statins, but conclusive evidence from controlled trials is lacking. After an 8-week placebo and diet run-in period, 30 persons with moderate hypercholesterolemia and untreated hypertension (total cholesterol 6.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
167
5
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(179 citation statements)
references
References 36 publications
5
167
5
2
Order By: Relevance
“…Previous studies have reported a BP-lowering effect of statins in hyperlipidaemic hypertensive patients who were not taking any antihypertensive drugs 6 and who had already received antihypertensive therapy. 7,8 However, the results of the present study clearly demonstrated that long-term use of pravastatin, simvastatin, fluvastatin, and nonstatin antihyperlipidaemic drug had no additional effect on BP but significantly decreased the serum TC levels in hypertensive patients with high serum TC levels and insufficiently controlled BP despite antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have reported a BP-lowering effect of statins in hyperlipidaemic hypertensive patients who were not taking any antihypertensive drugs 6 and who had already received antihypertensive therapy. 7,8 However, the results of the present study clearly demonstrated that long-term use of pravastatin, simvastatin, fluvastatin, and nonstatin antihyperlipidaemic drug had no additional effect on BP but significantly decreased the serum TC levels in hypertensive patients with high serum TC levels and insufficiently controlled BP despite antihypertensive therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that statins can be used to reduce BP in hypertensive patients with hypercholesterolaemia. [6][7][8] The mechanism of the reduction of BP by statins in hypertensive hyperlipidaemic patients involves the activation of endothelial nitric oxide synthase, 9 the downregulation of angiotensin II type 1 receptors, 10 and a reduction in the vascular production of reactive oxygen species. 11 In addition, the long-term administration of statins has been shown to inhibit the progression of aortic stenosis 12 and to reduce aortic stiffness, as assessed by PWV, in normotensive patients with hypercholesterolaemia.…”
Section: Introductionmentioning
confidence: 99%
“…12 In another study, there was no decrease in BP among normotensive subjects. 22 Glorioso et al 23 conducted a trial of pravastatin in 30 hypertensive, hypercholesterolemic subjects and demonstrated that, compared with placebo, treatment with pravastatin significantly decreased systolic, diastolic, and pulse pressures and blunted the BP increase induced by the cold pressor test.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the chronic use of antihypertensive agents, blood pressure was stable along the totality of the investigation and remained very close to normotensive values. Indeed, this situation did not allow the evaluation of whether statins might significantly reduce blood pressure, 23 but clearly showed that the PWV changes were roughly independent of blood pressure level, whether blood pressure was measured in the brachial or in the carotid arteries.…”
Section: Commentsmentioning
confidence: 99%